Modification of Environmental Factors on Quality of Sleep among Patients Admitted to CCU - Ahmad Ali Asadi Noghabi; Pouya Farokhnezhad Afshar; Mitra Zolfaghari; Mehdi Ajri Khameslou (Tehran University of Medical Sciences, 2012)
Background & Aim: Poor sleep quality is a common problem among patients hospitalized in the CCUs. This study aimed to determine the effect of environmental factors modification strategies on quality of sleep among patients admitted to CCU.Methods & Materials: This was a quasi-experimental study with a single-blinded design. Sixty patients admitted to the CCU of Shariati hospital were divided into two experiment and control groups. Sleep quality was measured in the first day of admission and three days later using the Pittsburgh sleep quality index in both groups. In the intervention group, we implemented a modified work environment between the two measurements. Data were analyzed using the Chi-squared and t-test in the SPSS v.18.Results: Findings showed a significant decrease in sleep quality in the control group after hospitalization, compared with the intervention group (P<0.001). There were no statistically significant changes in the sleep quality before and after hospitalization in the intervention group (P=0.053).Conclusion: Using environmental factors mitigation strategies can improve sleep quality of patients admitted to CCUs.